EVALUATING EARLY CHILDHOOD CHARACTER EDUCATION; FAMILY’S ROLE IN SHAPING A BRILLIANT GENERATION - nadila, sintha (JURNAL SETIA PANCASILA, 2025)
This research examines the importance of character education in early childhood and the roles that families, schools, and communities play in supporting it. The study highlights the responsibility of families in instilling moral values in children, such as honesty, responsibility, and empathy, through good communication and positive role models. Collaboration between families and schools is also emphasized as crucial in creating an environment that nurtures children's character development. The research adopts a descriptive approach and literature study to analyze the impact of character education on children's overall development. The findings indicate that effective character education helps children in managing emotions, building social skills, and preparing them to face future challenges. It emphasizes the need for consistent and continuous implementation of character education, involving all elements of society, to shape a superior and responsible next generation.